2020
DOI: 10.2174/1574884715666200110153125
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Juice does not Affect the Bioavailability of Cyclosporine in Healthy Thai Volunteers

Abstract: Background: It is still controversial whether pomegranate causes drug interactions. Pomegranate juice has been shown to inhibit CYP3A in-vitro and animal studies. The co-administration pomegranate juice with cyclosporine, a narrow therapeutic drug that is the substrate of CYP3A, which might lead to drug toxicity. The objective of this study is to investigate the effect of pomegranate juice on the pharmacokinetics of cyclosporine in healthy Thai volunteers. Methods: The study design was an open-label, rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A total of 300 μl of methanol/acetonitrile (50:50, v/v) and 50 μl of ZnSO4 solution were added, and the solution was vortexed for 30 s and centrifuged at 14,000 g (2000 rpm) for 10 min ( Figure 2 ). All the samples were stored at −20°C until further analysis ( Anlamlert and Sermsappasuk, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 300 μl of methanol/acetonitrile (50:50, v/v) and 50 μl of ZnSO4 solution were added, and the solution was vortexed for 30 s and centrifuged at 14,000 g (2000 rpm) for 10 min ( Figure 2 ). All the samples were stored at −20°C until further analysis ( Anlamlert and Sermsappasuk, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Many scientific reports have stated that pomegranate possesses antioxidant, anti-inflammatory ( Karwasra et al, 2019 ), anticancer, antidiabetic, antihypertensive, antifungal, nephroprotective ( Karwasra et al, 2016 ), antimalarial, and antiulcer properties ( Sreekumar et al, 2014 ). Several scientific publications also show that pomegranate juice and peel extracts showed interactions with diverse medications and could markedly increase/decrease the blood concentration of numerous drugs (theophylline, cyclosporine A, warfarin, carbamazepine, and TAC) in patients and rats ( Hidaka et al, 2005 ; Khuu et al, 2013 ; Alanbaki et al, 2019 ; Alnaqeeb et al, 2019 ; Anlamlert and Sermsappasuk, 2020 ). Despite numerous potential pharmacokinetic studies, none of the studies reported on the consumption of pomegranate rind extract (PRE) with TAC altering its pharmacokinetics and the impact of long-term consumption of PRE on TAC.…”
Section: Introductionmentioning
confidence: 99%
“…The effect from the GFJ was more pronounced (approximately twofold) than from the PJ. The review [12] further showed that most clinical studies that were done later showed no effect of PJ on flurbiprofen (an anti-inflammatory) [74], simvastatin [75], dapoxetine [76], midazolam [77], cyclosporine [78], and artemether [23].…”
Section: Food/juice-drug Interactions: Effect Of Pomegranate Juice On...mentioning
confidence: 99%
“…This shows that the observed preclinical inhibition of CYP3A4 and CYP2C9 by PJ does not necessarily relate to clinical drug interactions in humans [77]. This could be because most of the clinical studies were done using a single dose of PJ [12] and therefore, further clinical studies with prolonged PJ administration of the co-administered drugs are recommended.…”
Section: Food/juice-drug Interactions: Effect Of Pomegranate Juice On...mentioning
confidence: 99%